Factors influencing medical students’ knowledge and attitudes toward climate change: A cross-sectional study - Leen Oyoun Alsoud; Eman Alefishat; Cynthia Al Hageh; Saif M I Alkhaaldi; Ethan Jin; Maha Al Fahim; Rasha Buhumaid; Dima Abdelmannan; Halah Ibrahim (PLoS ONE, 2025)
Introduction Climate change is one of the biggest environmental challenges of the 21st century. Physicians are at the forefront of recognizing, preventing, and treating climate-induced health issues. This study aims to assess attitudes, education, and knowledge of recent medical graduates regarding climate change and its health impacts, and to identify factors influencing these domains. Materials & methods A cross-sectional web-based survey of recently graduated medical students was conducted at two large academic medical centers in the United Arab Emirates (UAE). Mean composite Likert scales were calculated. Linear regression models were utilized to study predictors of knowledge and attitude. Results Of 458 applicants to residency programs, 311 completed the survey (67.9% response rate). Most participants were female (n=206, 66.2%), aged 25 to 30 years (n=183, 58.8%), and attended medical schools in the Middle East and North Africa (MENA) region (n=209, 67.2%). The median knowledge score was 9 out of 14 (64.3%), with an IQR of 7 to 10. The mean attitude score was 50 out of 70 (71.4%), with an IQR of 44 to 54. These results suggest moderate levels of knowledge and generally positive attitudes. Most respondents (n=197, 63.3%) did not receive climate change education in medical school. Students who completed their education in the MENA region were the least likely to have received climate change education (16.75% vs. 46.94%; p <.001). Survey respondents who received education demonstrated significantly improved knowledge (β=1.23, p <.001). Having a higher knowledge composite score was positively associated with a higher composite attitude score (β=.71, p=.002). Conclusion Effects of climate change are particularly pronounced in the MENA region due to heat extremes, water scarcity, and air pollution. Recent medical graduates applying to residency programs in the UAE have had limited education in climate change. Medical schools around the world should prepare students to address the escalating health risks of climate change. This will require investing in faculty development, supporting student-led advocacy, adopting curriculum mapping tools, and most importantly, integrating clinical experience, such as project-based learning, simulations, and participatory action.